Laparoscopic Roux-en-Y gastric bypass versus single anastomosis sleeve ileal bypass for the treatment of morbidly obese patients: a prospective randomized comparative study - Arakeeb, Mohamed H.; El-sheikh, Mostafa M.; Elhady, Hamdy A.; Soliman, Soliman M.; Abdelhamid, Amir F. (International Surgery Journal, 2024)
Background: Bariatric surgery has proven to be the most effective long-term treatment of morbid obesity, after bariatric surgery, weight loss and remission of obesity-related comorbidities is significantly higher than after non-surgical measures. The present study aimed to compare single-anastomosis sleeve ileal (SASI) bypass and Roux-en-Y gastric bypass (RYGB) in terms of weight loss, remission of comorbidities, complications, and nutritional status. Methods: This prospective randomized comparative study was carried out at gastrointestinal and laparoscopic surgery unit, General Surgery Department, Tanta University Hospitals, during the period from October 2020 to October 2022 and included 40 morbidly obese patients who accepted to participate in the study and signed an informed consent. Patients were randomly assigned into 2 equal groups by the closed envelope method, group I: were submitted to laparoscopic RYGB, group II: were submitted to laparoscopic SASI bypass. Results: The mean age of RYGB group was 39.20±6.56 years, compared to 34.75±7.91 in SASI group. A highly statistically significant difference was present in operative time between both groups; RYGB Group had operative time mean of 194.25±27.11 minutes, compared to 153.15±23.74 minutes in SASI group. Both procedures were followed by a significant decrease in body mass index at 12 months and were comparable in terms of excess and total weight loss. Improvement in comorbidities after the two procedures was similar. Conclusions: RYGB and SASI bypass cause weight loss by both restriction and malabsorption mechanisms. Early results with the two procedures are encouraging with acceptable weight loss, comorbidity improvement rates with disadvantages as malnutrition, biliary reflux and dumping, yet the risk of malnutrition was more likely after SASI bypass.